KEARIFAN LOKAL LUBUK LARANGAN SEBAGAI UPAYA PELESTARIAN SUMBERDAYA PERAIRAN DI DESA PANGKALAN INDARUNG KABUPATEN KUANTAN SINGINGI - amri, Fauzul; Saam, Zulfan (Jurnal Kajian Lingkungan, 2013)
Pangkalan Indarung Village is one of the administrative villages in Singingi regency. Miningvillage with an area of 2000 hectares with a population of 2183 inhabitants. PangkalanIndarung Village has a shoreline area located on the River Singingi prohibition by 5 km longdevelopment (four location). The purpose of this study was to: 1). To know the local wisdomin applaying a tradition to the societies in river preserves 2). Analyze the Conservation Effortof the Aquatic. Lubuk Larangan is part of the river or lake is rather deep, sheltered, andpreferably fish as breeding grounds for various fish species, to allow the fish grow andreproduce naturally, and was banned for poaching within the specified time period.Themethod used is asurvey method of which goal is to gain data and information from agroup of people by observations, documentations, and direct interviews based on the preparedquestions; and the research has 19 notifiers consisting of highbrows, lowbrows, andgovernment. The research found the custom regulation which will keep Lubuk Larangan,i.e.:(1) etnotecnology/simple instrument, (2) planting and keeping vegetation throughout theriver’s course, (3) Forbidding to fish the Kaloso fish queens, and (4) The permitted fishes tofish are those of which weight 250 grams/fishes. (5) Lubuk